Secondary battery

The secondary battery design with a fluorine and boron-coated lithium composite oxide core and fluorine-containing electrolyte addresses safety issues by preventing excessive temperature rise and internal short circuits, maintaining high capacity and safety.

JP2025005813APending Publication Date: 2025-01-17MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023106192
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Secondary batteries face safety concerns due to insufficient safety measures, particularly during overcharging and internal short circuits, which can lead to excessive temperature rise and potential fires.

Method used

A secondary battery design featuring a positive electrode with a lithium composite oxide core coated by a layer containing lithium, fluorine, and boron, and an electrolyte using a fluorine-containing lithium salt, which suppresses excessive temperature rise by electrochemically protecting the core during charging.

Benefits of technology

The design ensures high battery capacity while significantly reducing the risk of overheating and internal short circuits, thereby enhancing safety and preventing potential fires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005813000001_ABST
    Figure 2025005813000001_ABST
Patent Text Reader

Abstract

To provide a secondary battery capable of obtaining excellent safety.SOLUTION: Positive electrode active material particles included in a positive electrode active material layer of a secondary battery each include a central portion including a lithium composite oxide and a covering portion provided on a surface of the central portion. The lithium composite oxide has a crystal structure of a layered rock salt type and includes lithium, nickel, and other elements as constituent elements. The covering portion includes lithium, fluorine, boron, and oxygen as constituent elements. An electrolyte salt includes a fluorine-containing lithium salt. A content of the nickel in the lithium composite oxide is 80 parts by mol or more and 100 parts by mol or less. A first negative secondary ion derived from LiF2- and a second negative secondary ion derived from BO2- are detected in analysis in a depth direction of the positive electrode active material layer using time-of-flight secondary ion mass spectrometry. A second peak of the second negative secondary ion in the depth direction is located on a deeper side than a first peak of the first negative secondary ion in the depth direction.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a secondary battery. [Background technology]

[0002] Due to the widespread use of various electronic devices such as mobile phones, secondary batteries have been developed as power sources that are small and lightweight and can provide high energy density. These secondary batteries include a positive electrode, a negative electrode, and an electrolyte solution, and various studies have been conducted on the configuration of the secondary battery.

[0003] Specifically, a coating portion is formed on the surface of nickel-containing lithium composite transition metal oxide particles, and the coating portion contains fluorine (see, for example, Patent Document 1). High concentration of fluorine exists on the surface of nickel-containing composite oxide particles (see, for example, Patent Document 2). The positive electrode active material contains lithium transition metal oxide, and a peak derived from boron is detected in depth analysis of the positive electrode active material by time-of-flight secondary ion mass spectrometry (see, for example, Patent Document 3). By charging and discharging the assembled battery under heating, ions such as lithium borate ions are detected in surface analysis of the negative electrode active material after initial charging and discharging using time-of-flight secondary ion mass spectrometry (see, for example, Patent Document 4). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2022-525463 [Patent Document 2] JP 2006-351487 A [Patent Document 3] JP 2015-099659 A [Patent Document 4] JP 2013-062026 A Summary of the Invention [Problem to be solved by the invention]

[0005] Although various studies have been conducted on the configuration of secondary batteries, the safety of the secondary batteries is still insufficient and there is room for improvement.

[0006] There is a demand for a secondary battery that can provide excellent safety. [Means for solving the problem]

[0007] A secondary battery according to an embodiment of the present technology includes a positive electrode including a positive electrode active material layer, a negative electrode, and an electrolyte solution including an electrolyte salt. The positive electrode active material layer includes a plurality of positive electrode active material particles, and the positive electrode active material particles include a center portion including a lithium composite oxide and a coating portion provided on the surface of the center portion. The lithium composite oxide has a layered rock salt type crystal structure and includes lithium, nickel, and other elements as constituent elements. The coating portion includes lithium, fluorine, boron, and oxygen as constituent elements. The electrolyte salt includes a fluorine-containing lithium salt. When the sum of the content of nickel in the lithium composite oxide and the content of other elements in the lithium composite oxide is 100 molar parts, the content of nickel in the lithium composite oxide is 80 molar parts or more and 100 molar parts or less. In an analysis of the positive electrode active material layer in the depth direction using time-of-flight secondary ion mass spectrometry, LiF2 - The first negative secondary ions and BO2 - Second negative secondary ions derived from the first negative secondary ions are detected. The change in ion intensity of the first negative secondary ions in the depth direction has a first peak, and the change in ion intensity of the second negative secondary ions in the depth direction has a second peak. The second peak is located deeper than the first peak in the depth direction.

[0008] Here, as described above, the lithium composite oxide is a general term for oxides that have a layered rock salt type crystal structure and contain lithium, nickel and other elements as constituent elements, and the other elements are any one or more of elements other than lithium and nickel.Furthermore, the fluorine-containing lithium salt is a general term for lithium salts that contain fluorine as a constituent element.The details of the respective structures of the lithium composite oxide and the fluorine-containing lithium salt will be described later. Effect of the Invention

[0009] According to a secondary battery of one embodiment of the present technology, a positive electrode active material layer of a positive electrode includes a plurality of positive electrode active material particles, the positive electrode active material particles include a center portion and a coating portion, the center portion includes a lithium composite oxide, the lithium composite oxide has a layered rock salt type crystal structure and includes lithium, nickel and other elements as constituent elements, the coating portion includes lithium, fluorine, boron and oxygen as constituent elements, the electrolyte salt of the electrolyte solution includes a fluorine-containing lithium salt, the nickel content in the lithium composite oxide is 80 molar parts or more and 100 molar parts or less, and an analysis of the positive electrode active material layer in the depth direction using time-of-flight secondary ion mass spectrometry reveals that LiF2 - The first negative secondary ions and BO2 - A second negative secondary ion derived from the first negative secondary ion is detected, and the second peak in the change in ionic intensity of the second negative secondary ion is located deeper in the depth direction than the first peak in the change in ionic intensity of the first negative secondary ion, thereby providing excellent safety.

[0010] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a perspective view illustrating a configuration of a secondary battery according to an embodiment of the present technology. [Diagram 2]FIG. 2 is a cross-sectional view illustrating the configuration of the battery element shown in FIG. [Diagram 3] FIG. 3 is a cross-sectional view showing the configuration of a positive electrode active material particle. [Figure 4] FIG. 4 is a cross-sectional view that typically illustrates the configuration of the positive electrode active material particle shown in FIG. [Diagram 5] FIG. 5 shows an example of the results of analysis of the positive electrode active material layer in the depth direction using time-of-flight secondary ion mass spectrometry. [Figure 6] FIG. 6 shows another example of the analysis results of the positive electrode active material layer in the depth direction using time-of-flight secondary ion mass spectrometry. [Figure 7] FIG. 7 is a cross-sectional view illustrating a method for manufacturing a secondary battery. [Figure 8] FIG. 8 is a cross-sectional view showing the configuration of a test secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Secondary battery 1-1. Overall structure 1-2. Detailed composition of positive electrode active material particles 1-3. Properties of the positive electrode 1-4.Operation 1-5. Manufacturing method 1-6. Actions and Effects 2. Variations 3. Uses of secondary batteries

[0013] <1. Secondary battery> First, a secondary battery according to an embodiment of the present technology will be described.

[0014] The secondary battery described here is a secondary battery in which battery capacity is obtained by utilizing the absorption and release of an electrode reactant, and is provided with a positive electrode, a negative electrode, and an electrolyte.

[0015] The charge capacity of the negative electrode is preferably larger than the discharge capacity of the positive electrode. That is, the electrochemical capacity per unit area of ​​the negative electrode is preferably larger than the electrochemical capacity per unit area of ​​the positive electrode. This is to prevent deposition of an electrode reactant on the surface of the negative electrode during charging.

[0016] The type of the electrode reactant is not particularly limited, but specifically, it is a light metal such as an alkali metal or an alkaline earth metal. Specific examples of the alkali metal include lithium, sodium, and potassium, and specific examples of the alkaline earth metal include beryllium, magnesium, and calcium.

[0017] In the following, an example will be given in which the electrode reactant is lithium. A secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In this lithium ion secondary battery, lithium is absorbed and released in an ionic state.

[0018] <1-1. Overall composition> Fig. 1 shows a perspective view of a secondary battery. Fig. 2 shows a cross-sectional view of a battery element 20 shown in Fig. 1. Fig. 3 shows a cross-sectional view of a positive electrode active material particle 210.

[0019] 1 shows a state in which the exterior film 10 and the battery element 20 are separated from each other, and a cross section of the battery element 20 taken along the XZ plane is shown by a dashed line. In FIG. 2, only a part of the battery element 20 is shown.

[0020] As shown in FIGS. 1 and 2, this secondary battery includes an exterior film 10, a battery element 20, a positive electrode lead 31, a negative electrode lead 32, and sealing films 41 and .

[0021] As described above, the secondary battery described here uses a flexible or pliable exterior film 10 as an exterior member for housing the battery element 20. Therefore, the secondary battery shown in Fig. 1 is a so-called laminate film type secondary battery.

[0022] [Exterior film] 1, the exterior film 10 has a bag-like structure that is sealed when the battery element 20 is housed therein. As a result, the exterior film 10 houses a positive electrode 21, a negative electrode 22, and a separator 23, which will be described later.

[0023] Here, the exterior film 10 is a single film-like member, and is folded in a folding direction F. This exterior film 10 is provided with a recessed portion 10U for accommodating the battery element 20, and this recessed portion 10U is a so-called deep drawn portion.

[0024] Specifically, the exterior film 10 is a three-layer laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order from the inside, and when the exterior film 10 is folded, the outer peripheral edges of the opposing fusion layers are fused to each other. The fusion layer contains a polymer compound such as polypropylene. The metal layer contains a metal material such as aluminum. The surface protection layer contains a polymer compound such as nylon.

[0025] However, the configuration (number of layers) of the exterior film 10 is not particularly limited, and may be one or two layers, or may be four or more layers.

[0026] [Battery element] The battery element 20 is housed in a bag-shaped exterior film 10. The battery element 20 is a so-called power generating element, and includes a positive electrode 21, a negative electrode 22, and a separator 23, as shown in Figs.

[0027] Here, since the battery element 20 is a so-called wound electrode body, the positive electrode 21 and the negative electrode 22 are wound around a winding axis P while facing each other via a separator 23. This winding axis P is an imaginary axis extending in the Y-axis direction.

[0028] There is no particular limitation on the three-dimensional shape of the battery element 20. Here, the battery element 20 has a flat three-dimensional shape, and therefore the shape of a cross section (cross section along the XZ plane) of the battery element 20 intersecting with the winding axis P is a flat shape defined by the major axis J1 and the minor axis J2.

[0029] The long axis J1 is an imaginary axis extending in the X-axis direction and has a length greater than that of the short axis J2. The short axis J2 is an imaginary axis extending in the Z-axis direction intersecting with the X-axis direction and has a length smaller than that of the long axis J1. Here, the three-dimensional shape of the battery element 20 is a flattened cylinder, and therefore the cross-sectional shape of the battery element 20 is a flattened, approximately elliptical shape.

[0030] (positive electrode) As shown in FIG. 2, the positive electrode 21 includes a positive electrode active material layer 21B.

[0031] Here, the positive electrode 21 further includes a positive electrode current collector 21A that supports the positive electrode active material layer 21B. However, the positive electrode current collector 21A may be omitted.

[0032] The positive electrode current collector 21A is a conductive member, and has a pair of surfaces on which the positive electrode active material layer 21B is provided. The positive electrode current collector 21A contains a conductive material such as a metal material, and a specific example of the conductive material is aluminum.

[0033] The positive electrode active material layer 21B contains one or more types of positive electrode active materials that absorb and release lithium. However, the positive electrode active material layer 21B may further contain one or more types of other materials such as a positive electrode binder, a positive electrode conductive agent, and a dispersant. The method for forming the positive electrode active material layer 21B is not particularly limited, but specifically includes a coating method.

[0034] Here, the positive electrode active material layer 21B is provided on both sides of the positive electrode current collector 21A. However, the positive electrode active material layer 21B may be provided on only one side of the positive electrode current collector 21A on the side where the positive electrode 21 faces the negative electrode 22.

[0035] Specifically, as shown in Fig. 3, the positive electrode active material layer 21B contains a plurality of particulate positive electrode active materials (hereinafter referred to as "a plurality of positive electrode active material particles 210"), and the positive electrode active material particles 210 include a central portion 211 and a coating portion 212. The details of the configuration of the positive electrode active material particles 210 will be described later (see Fig. 4).

[0036] The positive electrode binder is a material that bonds particles such as the positive electrode active material particles 210 to each other, and contains one or more of materials such as synthetic rubber and polymer compounds. Specific examples of synthetic rubber include styrene butadiene rubber, fluorine-based rubber, and ethylene propylene diene. Specific examples of polymer compounds include polyvinylidene fluoride, polyimide, and carboxymethyl cellulose.

[0037] The positive electrode conductive agent is a material that improves the conductivity of the positive electrode active material layer 21B, and contains one or more conductive materials such as carbon materials, metal materials, and conductive polymer compounds. Specific examples of carbon materials include graphite, carbon black, acetylene black, and ketjen black.

[0038] The dispersant is a material that improves the dispersibility of particles such as the positive electrode active material in the secondary battery manufacturing process (preparation process of the positive electrode mixture slurry) described later, and contains one or more types of polymer compounds such as polyvinylpyrrolidone.

[0039] In this secondary battery, three types of physical property conditions are satisfied with respect to the physical properties of the positive electrode 21, and the details of the three types of physical property conditions will be described later.

[0040] (Negative electrode) As shown in FIG. 2, the negative electrode 22 includes a negative electrode current collector 22A and a negative electrode active material layer 22B.

[0041] The negative electrode current collector 22A is a conductive member that supports the negative electrode active material layer 22B, and has a pair of surfaces on which the negative electrode active material layer 22B is provided. The negative electrode current collector 22A contains a conductive material such as a metal material, and a specific example of the conductive material is copper.

[0042] The negative electrode active material layer 22B includes one or more types of negative electrode active materials that absorb and release lithium. However, the negative electrode active material layer 22B may further include one or more types of other materials such as a negative electrode binder and a negative electrode conductive agent. The method for forming the negative electrode active material layer 22B is not particularly limited, and specifically includes one or more types of a coating method, a gas phase method, a liquid phase method, a thermal spraying method, and a baking method (sintering method).

[0043] Here, the negative electrode active material layer 22B is provided on both sides of the negative electrode current collector 22A. However, the negative electrode active material layer 22B may be provided on only one side of the negative electrode current collector 22A on the side where the negative electrode 22 faces the positive electrode 21.

[0044] The type of the negative electrode active material is not particularly limited, but specifically includes carbon materials and metal-based materials, etc., because a high energy density can be obtained.

[0045] Specific examples of the carbon material include graphitizable carbon, non-graphitizable carbon, graphite, etc. The graphite may be natural graphite or artificial graphite.

[0046] A metallic material is a material that contains, as a constituent element, one or more of metallic elements and semi-metallic elements that can form an alloy with lithium, and specific examples of the metallic elements and semi-metallic elements include silicon and tin. This metallic material may be a simple substance, an alloy, a compound, a mixture of two or more of these, or a material containing two or more of these phases. However, the simple substances described here may contain any amount of impurities, and therefore the purity of the simple substances is not necessarily limited to 100%. Specific examples of metallic materials are TiSi2 and SiO x(0 <x≦2または0.2<x<1.4)などである。

[0047] The details regarding the negative electrode binder are the same as those regarding the positive electrode binder, and the details regarding the negative electrode conductive agent are the same as those regarding the positive electrode conductive agent.

[0048] (Separator) 2, the separator 23 is an insulating porous film interposed between the positive electrode 21 and the negative electrode 22, and allows lithium to pass through in an ionized state while preventing the occurrence of a short circuit due to contact between the positive electrode 21 and the negative electrode 22. The separator 23 contains one or more types of polymer compounds such as polyethylene.

[0049] (electrolyte) The electrolyte solution, which is a liquid electrolyte, contains an electrolyte salt and is impregnated into each of the positive electrode 21, the negative electrode 22, and the separator 23. Here, the electrolyte solution further contains a solvent that dissolves or disperses the electrolyte salt.

[0050] The electrolyte salt contains one or more of the fluorine-containing lithium salts, which is a general term for lithium salts containing fluorine as a constituent element, as described above. Since the fluorine-containing lithium salt contains an anion together with a lithium ion, which is a cation, fluorine is contained in the anion as a constituent element.

[0051] The reason why the electrolyte salt contains the fluorine-containing lithium salt is as follows. First, the cation (lithium ion) of the fluorine-containing lithium salt functions as an electrode reactant, so that a high battery capacity can be obtained. Second, as described below, in a stabilization process of the secondary battery after assembly, the fluorine contained as a constituent element in the fluorine-containing lithium salt is utilized to promote a reaction for forming hydrogen fluoride, so that the precursor coating portion 212Z is ​​converted into the upper coating portion 212A.

[0052] The type of fluorine-containing lithium salt is not particularly limited as long as the anion contains fluorine as a constituent element.Specific examples of fluorine-containing lithium salt include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (LiN(FSO2)2), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium tris(trifluoromethanesulfonyl)methide (LiC(CF3SO2)3), lithium difluoro(oxalato)borate (LiBF2(C2O4)), lithium monofluorophosphate (Li2PFO3) and lithium difluorophosphate (LiPF2O2).

[0053] Among these, it is preferable that the fluorine-containing lithium salt contains one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, because the precursor coating portion 212Z is ​​easily converted into the upper coating portion 212A by using the fluorine-containing lithium salt.

[0054] The content of the electrolyte salt in the electrolytic solution is not particularly limited, but specifically, it is 0.3 mol / kg to 3.0 mol / kg relative to the solvent, because high ionic conductivity can be obtained.

[0055] The electrolyte salt may further contain one or more of other lithium salts. The other lithium salts are lithium salts that do not contain fluorine as a constituent element, and a specific example of the other lithium salts is lithium bis(oxalato)borate (LiB(C2O4)2).

[0056] The solvent contains one or more types of non-aqueous solvents (organic solvents), and the electrolyte containing the non-aqueous solvent is a so-called non-aqueous electrolyte.

[0057] The non-aqueous solvent is an ester or an ether, more specifically, a carbonate compound, a carboxylate compound, a lactone compound, etc. This is because the dissociation property of the electrolyte salt is improved and the mobility of ions is also improved.

[0058] The carbonate ester compounds are cyclic carbonate esters and chain carbonate esters. Specific examples of the cyclic carbonate esters include ethylene carbonate and propylene carbonate, and specific examples of the chain carbonate esters include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0059] The carboxylate compounds include chain carboxylates, and specific examples of the chain carboxylates include ethyl acetate, ethyl propionate, propyl propionate, and ethyl trimethylacetate. The lactone compounds include lactones, and specific examples of the lactones include γ-butyrolactone and γ-valerolactone.

[0060] The ethers may be 1,2-dimethoxyethane, tetrahydrofuran, 1,3-dioxolane, and 1,4-dioxane.

[0061] The electrolytic solution may further contain one or more of the additives.

[0062] Specifically, the additive is preferably a boron-fluorine-containing material, which is a general term for compounds that contain boron and fluorine as constituent elements.

[0063] When the electrolyte contains a boron-fluorine containing material, as described below, during the stabilization treatment of the secondary battery after assembly, the reaction of forming hydrogen fluoride is more likely to proceed using the fluorine contained as a constituent element in the boron-fluorine containing material, and therefore the precursor coating portion 212Z is ​​more likely to be converted into the upper coating portion 212A.

[0064] As long as the boron-fluorine-containing material contains boron and fluorine as constituent elements, the type of the boron-fluorine-containing material is not particularly limited. Specific examples of the boron-fluorine-containing material include lithium tetrafluoroborate and lithium difluoro(oxalato)borate. This is because the precursor coating portion 212Z is ​​sufficiently converted into the upper coating portion 212A by using the boron-fluorine-containing material.

[0065] The additives are unsaturated cyclic carbonates, fluorinated cyclic carbonates, sulfonates, phosphates, acid anhydrides, nitrile compounds and isocyanate compounds, because they improve the electrochemical stability of the electrolyte.

[0066] Specific examples of unsaturated cyclic carbonates include vinylene carbonate, vinylethylene carbonate, and methyleneethylene carbonate. Specific examples of fluorinated cyclic carbonates include monofluoroethylene carbonate and difluoroethylene carbonate. Specific examples of sulfonic acid esters include propane sultone and propene sultone. Specific examples of phosphate esters include trimethyl phosphate and triethyl phosphate. Specific examples of acid anhydrides include succinic anhydride, 1,2-ethanedisulfonic anhydride, and 2-sulfobenzoic anhydride. Specific examples of nitrile compounds include succinonitrile. Specific examples of isocyanate compounds include hexamethylene diisocyanate.

[0067] [Positive lead] 1 and 2, the positive electrode lead 31 is a positive electrode wiring connected to the positive electrode current collector 21A of the positive electrode 21, and is led out of the exterior film 10. The positive electrode lead 31 contains a conductive material such as a metal material, and a specific example of the conductive material is aluminum. The positive electrode lead 31 has a shape of a thin plate or a mesh.

[0068] [Negative lead] As shown in Figs. 1 and 2, the negative electrode lead 32 is a negative electrode wiring connected to the negative electrode current collector 22A of the negative electrode 22, and is led out of the exterior film 10. Here, the lead-out direction of the negative electrode lead 32 is the same as the lead-out direction of the positive electrode lead 31. This negative electrode lead 32 contains a conductive material such as a metal material, and a specific example of the conductive material is copper. The details of the shape of the negative electrode lead 32 are the same as the details of the shape of the positive electrode lead 31.

[0069] [Sealing film] The sealing film 41 is inserted between the exterior film 10 and the positive electrode lead 31, and the sealing film 42 is inserted between the exterior film 10 and the negative electrode lead 32. However, one or both of the sealing films 41 and 42 may be omitted.

[0070] The sealing film 41 is a sealing member that prevents outside air and foreign matter from entering the inside of the exterior film 10. This sealing film 41 contains a polymer compound such as polyolefin that has adhesion to the positive electrode lead 31, and a specific example of the polymer compound is polypropylene.

[0071] The configuration of the sealing film 42 is similar to the configuration of the sealing film 41, except that the sealing film 42 is a sealing member having adhesion to the negative electrode lead 32. That is, the sealing film 42 contains a polymer compound such as polyolefin having adhesion to the negative electrode lead 32.

[0072] <1-2. Detailed composition of positive electrode active material particles> Fig. 4 shows a schematic cross-sectional configuration of the positive electrode active material particle 210 shown in Fig. 3. In Fig. 4, only a portion of the positive electrode active material particle 210 near the surface is shown.

[0073] As described above, the positive electrode active material particle 210 includes the core portion 211 and the coating portion 212.

[0074] [Center] As shown in FIG. 3, the core portion 211 contains one or more types of lithium composite oxides.

[0075] (Lithium composite oxide) The lithium composite oxide is a substance that absorbs and releases lithium. As described above, the lithium composite oxide is a general term for oxides that have a layered rock-salt crystal structure and contain lithium, nickel, and other elements as constituent elements. The other elements are one or more of elements other than lithium and nickel.

[0076] The type of other element is not particularly limited as long as it is an element belonging to Groups 2 to 15 of the long periodic table. Specific examples of other elements include cobalt, aluminum, manganese, zirconium, titanium, molybdenum, tantalum, chromium, niobium, iron, copper, zinc, vanadium, magnesium, tungsten, sulfur, strontium, boron, sodium, and fluorine. This is because sufficient battery capacity can be obtained.

[0077] A specific example of a lithium composite oxide is LiNi 0.86 Co 0.10 Mn 0.04 O2, LiNi 0.88 Co 0.10 Al 0.02 O2 and LiNi 0.90 Co 0.08 Mn 0.01 Al 0.01 O2, etc.

[0078] (Content percentage) In this lithium composite oxide, the nickel content is set to be sufficiently large. Specifically, when the sum of the nickel content in the lithium composite oxide and the contents of other elements in the lithium composite oxide is taken as 100 parts by mol, the nickel content is 80 parts by mol to 100 parts by mol.

[0079] As is clear from the fact that the upper limit of the nickel content is 100 parts by mole, the lithium composite oxide may or may not contain other elements as constituent elements.

[0080] When the lithium composite oxide contains two or more kinds of other elements as constituent elements, the content of the other elements in the above-mentioned lithium composite oxide is the sum of the respective contents of the two or more kinds of other elements contained as constituent elements in the lithium composite oxide.

[0081] In other words, if the nickel content in the lithium composite oxide is C1 (mol) and the other element content in the lithium composite oxide is C2 (mol), the nickel content C calculated based on the formula C=[C1 / (C1+C2)]×100 is 80 mol% to 100 mol%.

[0082] The content is 80 mol % to 100 mol % because the potential for absorbing and releasing lithium is lowered compared to when the content is less than 80 mol %, and therefore a high battery capacity can be obtained.

[0083] (Procedure for identifying content ratio) The procedure for specifying the content ratio is as follows: In the following, a case where the positive electrode active material layer 21B contains a positive electrode active material (a plurality of positive electrode active material particles 210) and a positive electrode binder will be described.

[0084] First, the secondary battery is disassembled to recover the positive electrode 21, and then the positive electrode 21 is washed with a washing solvent. The type of the washing solvent is not particularly limited, but specifically, it is an organic solvent such as dimethyl carbonate. This removes the electrolyte attached to the positive electrode 21.

[0085] Next, the positive electrode 21 is immersed in a solvent for dissolving and removing. The type of the solvent for dissolving and removing is not particularly limited, but specifically, N-methyl-2-pyrrolidone capable of dissolving the positive electrode binder is used. As a result, the positive electrode binder contained in the positive electrode active material layer 21B is dissolved, and the positive electrode current collector 21A is peeled off from the positive electrode active material layer 21B.

[0086] Next, the positive electrode current collector 21A is taken out from the solvent for solvent removal, and the solvent for dissolving and removing is filtered to recover a filtrate that is a solid matter. This removes the solvent for dissolving and removing in which the positive electrode binder is dissolved, and thus a plurality of positive electrode active material particles 210 that are the filtrate are obtained.

[0087] Next, the positive electrode active material particles 210 are analyzed using one or more of analytical methods such as inductively coupled plasma (ICP) emission spectrometry. In this case, the composition of the lithium composite oxide contained in the core portion 211 is analyzed, and the contents (mol) of a series of constituent elements contained in the lithium composite oxide are measured. This allows each of the contents C1 and C2 to be identified.

[0088] Finally, the content ratio C is calculated based on the contents C1 and C2 using the above-mentioned formula.

[0089] (chemical formula) More specifically, the lithium composite oxide contains one or more of the compounds represented by formula (1), and the compound represented by formula (1) contains another element E as a constituent element.

[0090] Li a Ni b E 1-b O2···(1) (E is one or more of Co, Al, Mn, Zr, Ti, Mo, Ta, Cr, Nb, Fe, Cu, Zn, V, Mg, W, S, Sr, B, Na, and F. a and b satisfy 0.8≦a≦1.05 and 0.8≦b≦1.0.)

[0091] (Lithium-containing compounds) The core 211 may further contain one or more of lithium-containing compounds that absorb and release lithium. The lithium-containing compound is a general term for compounds that contain lithium as a constituent element, and the lithium composite oxide described above is excluded from the lithium-containing compounds described here.

[0092] The lithium-containing compound is a compound containing lithium and one or more kinds of transition metal elements as constituent elements, and may further contain one or more kinds of additional elements as constituent elements. The type of the additional element is not particularly limited as long as it is an element other than lithium and transition metals, and specifically, it is an element belonging to Groups 2 to 15 of the long periodic table. The type of the lithium-containing compound is not particularly limited, and specifically, it is an oxide, a phosphate compound, a silicate compound, a borate compound, etc.

[0093] Specific examples of oxides are LiCoO2, LiCo 0.98 Al 0.01 Mg 0.01 Specific examples of phosphate compounds include LiFePO4, LiMnPO4 and LiFe 0.5 Mn 0.5 PO4, etc.

[0094] [Coating] As shown in FIG. 3, covering portion 212 is provided on the surface of center portion 211, and therefore covers the surface of center portion 211.

[0095] Here, covering portion 212 covers the entire surface of central portion 211. However, covering portion 212 may cover only a portion of the surface of central portion 211. In this case, a plurality of covering portions 212 separated from one another may cover the surface of central portion 211.

[0096] (composition) As described later, in an analysis of the positive electrode active material layer 21B in the depth direction D using time-of-flight secondary ion mass spectrometry (TOF-SIMS), the coating portion 212 was found to contain LiF2 - The first negative secondary ions and BO2 - The material includes a material from which second negative secondary ions derived from the above-described second negative secondary ions are detected. The analysis of the positive electrode active material layer 21B in the depth direction D using the TOF-SIMS described here is a so-called depth analysis.

[0097] Thus, the coating portion 212 contains lithium, fluorine, boron, and oxygen as constituent elements. The composition of the material forming the coating portion 212 is not particularly limited as long as the first negative secondary ions and the second negative secondary ions can be detected in the depth analysis of the positive electrode active material layer 21B using the above-mentioned TOF-SIMS.

[0098] The coating portion 212 is provided on the surface of the central portion 211, and the coating portion 212 contains lithium, fluorine, boron, and oxygen as constituent elements because heat generation in the positive electrode 21 during charging is suppressed, thereby suppressing an excessive temperature rise in the positive electrode 21. In this case, as described below, three types of physical property conditions are satisfied regarding the physical properties of the positive electrode 21, so that even if the central portion 211 contains a lithium composite oxide and the content ratio of the lithium composite oxide is 80 mol % or more, an excessive temperature rise in the positive electrode 21 is effectively suppressed.

[0099] In detail, as described above, the core portion 211 contains a lithium composite oxide, and the content of the lithium composite oxide is 80 mol % or more, so that a high battery capacity can be obtained.

[0100] However, if the content of the lithium composite oxide is 80 mol % or more, the crystal structure of the lithium composite oxide becomes unstable during charging, and in this case, the temperature of the lithium composite oxide is likely to rise excessively when a minute internal short circuit or the like occurs inside the secondary battery.

[0101] When the temperature of the lithium composite oxide rises excessively, the crystal structure of the lithium composite oxide collapses, and oxygen and heat are released from the lithium composite oxide. This collapse of the crystal structure is particularly likely to occur near the surface of the lithium composite oxide that is in contact with the electrolyte.

[0102] For these reasons, when the content of the lithium composite oxide is 80 mol % or more, a high battery capacity can be obtained, but the exothermic reaction in the central portion 211 proceeds at an accelerated rate, so that the temperature of the positive electrode 21 tends to rise excessively. This may induce problems such as fire in the secondary battery.

[0103] In contrast, a coating portion 212 containing lithium, fluorine, boron and oxygen as constituent elements is provided on the surface of the central portion 211, and when three types of physical property conditions are satisfied regarding the physical properties of the positive electrode 21, the surface of the central portion 211 is electrochemically properly protected by the coating portion 212.

[0104] In this case, even if the content of the lithium composite oxide is 80 mol % or more, the crystal structure of the lithium composite oxide is unlikely to collapse during charging, so that the lithium composite oxide is unlikely to release oxygen and heat, and therefore the temperature of the lithium composite oxide is unlikely to rise excessively.

[0105] For these reasons, since the content of the lithium composite oxide is 80 mol % or more, not only is a high battery capacity obtained, but also the exothermic reaction is less likely to proceed in the central portion 211, so that the temperature of the positive electrode 21 is less likely to rise excessively. Thus, while the battery capacity is guaranteed, an excessive rise in temperature of the positive electrode 21 is suppressed during overcharging, heating of the secondary battery, and occurrence of an internal short circuit. This makes it less likely that problems such as fire will occur in the secondary battery.

[0106] (Specific configuration) Here, as described above, the coating portion 212 contains lithium, fluorine, boron, and oxygen as constituent elements so as to enable detection of the first negative secondary ions and the second negative secondary ions in the depth analysis of the positive electrode active material layer 21B using TOF-SIMS, and the configuration of the coating portion 212 is not particularly limited as long as three types of physical property conditions are satisfied regarding the physical properties of the positive electrode 21.

[0107] Specifically, as shown in Fig. 4, covering portion 212 preferably includes upper covering portion 212A and lower covering portion 212B. That is, covering portion 212 preferably has a two-layer structure in which upper covering portion 212A and lower covering portion 212B are laminated in this order from the side farthest from center portion 211. This is because the three types of physical property conditions are more likely to be satisfied with respect to the physical properties of positive electrode 21, and thus a rise in temperature of positive electrode 21 is sufficiently suppressed.

[0108] 4, the configurations of center portion 211, upper covering portion 212A, and lower covering portion 212B are simplified to make them easier to see. That is, to simplify the content of the drawing, center portion 211, upper covering portion 212A, and lower covering portion 212B are shown as having a simple three-layer structure.

[0109] However, the boundary between the upper covering portion 212A and the lower covering portion 212B does not have to be clear. In this case, part of the constituent material of the upper covering portion 212A may diffuse into the lower covering portion 212B, or part of the constituent material of the lower covering portion 212B may diffuse into the upper covering portion 212A, so the boundary between the upper covering portion 212A and the lower covering portion 212B may be unclear.

[0110] Of course, since a portion of the constituent material of upper covering portion 212A diffuses into lower covering portion 212B, and a portion of the constituent material of lower covering portion 212B diffuses into upper covering portion 212A, the constituent materials of upper covering portion 212A and lower covering portion 212B may diffuse into each other.

[0111] In this case, due to the above-mentioned diffusion, one or more intermediate layers may be interposed between upper covering portion 212A and lower covering portion 212B. The configuration of this intermediate layer is not particularly limited, but as an example, the intermediate layer contains both the constituent material of upper covering portion 212A and the constituent material of lower covering portion 212B.

[0112] (Upper covering part) The upper covering portion 212A is a first covering portion that is disposed farther from the center portion 211 than the lower covering portion 212B.

[0113] This upper covering portion 212A preferably contains lithium and fluorine as constituent elements in order to enable detection of the first negative secondary ions in the depth analysis of the positive electrode active material layer 21B using the above-mentioned TOF-SIMS. This is because the surface of the center portion 211 is more likely to be electrochemically and appropriately protected by the covering portion 212.

[0114] Of these, it is more preferable that upper covering portion 212A contains lithium fluoride (LiF), because this makes it easier to form upper covering portion 212A and also ensures that the surface of center portion 211 is sufficiently electrochemically protected by covering portion 212.

[0115] Here, upper covering portion 212A is formed on the surface of lower covering portion 212B by using a stabilization treatment (initial charge / discharge treatment) of the assembled secondary battery in the manufacturing process of the secondary battery, as described later. The method of forming upper covering portion 212A will be described in detail later.

[0116] To confirm that the upper coating portion 212A contains lithium and fluorine as constituent elements, a plurality of positive electrode active material particles 210 may be recovered from the secondary battery (positive electrode 21) using a procedure similar to the procedure for determining the content ratio described above, and then the positive electrode active material particles 210 (upper coating portion 212A) may be analyzed.

[0117] The method for analyzing upper covering portion 212A is not particularly limited, and therefore any one or more of any analysis methods can be used as the method for analyzing upper covering portion 212A.

[0118] Specifically, the composition of the upper covering portion 212A may be analyzed by performing a depth direction analysis of the positive electrode active material particles 210 using Auger electron spectroscopy (AES). Alternatively, the positive electrode 21 may be processed using focused ion beam processing (FIB) or the like to obtain a slice including the upper covering portion 212A, and then the slice may be analyzed using transmission electron microscopy-electron energy loss spectroscopy (TEM-EELS) to analyze the composition of the upper covering portion 212A.

[0119] (Lower covering part) The lower covering portion 212B is a second covering portion that is disposed closer to the center portion 211 than the upper covering portion 212A.

[0120] In order to enable detection of the second negative secondary ions in the depth analysis of the positive electrode active material layer 21B using the above-mentioned TOF-SIMS, it is preferable that the lower covering portion 212B contains lithium, boron, and oxygen as constituent elements. This is because the surface of the center portion 211 is more likely to be electrochemically and appropriately protected by the covering portion 212.

[0121] In particular, it is more preferable that lower covering portion 212B contains lithium metaborate (LiBO2), because this makes it easier to form lower covering portion 212B and also ensures that the surface of center portion 211 is sufficiently electrochemically protected by covering portion 212.

[0122] The procedure for confirming that the lower coating portion 212B contains lithium, boron and oxygen as constituent elements is similar to the procedure for confirming that the upper coating portion 212A contains lithium and fluorine as constituent elements described above, except that the lower coating portion 212B is analyzed instead of the upper coating portion 212A.

[0123] <1-3. Properties of the positive electrode> As described above, in this secondary battery, the properties of the positive electrode 21, more specifically, the properties of the positive electrode active material layer 21B satisfy three types of property conditions (the first property condition, the second property condition, and the third property condition).

[0124] In the following, a case will be described in which covering portion 212 includes upper covering portion 212A (lithium fluoride) and lower covering portion 212B (lithium metaborate).

[0125] [Depth analysis of the positive electrode active material layer using TOF-SIMS] 5 and 6 each show an example of an analysis result of positive electrode active material layer 21B using TOF-SIMS in depth direction D. The horizontal axis indicates sputtering time (seconds) and the vertical axis indicates ion intensity (counts).

[0126] Using TOF-SIMS, a depth analysis is performed on the positive electrode active material layer 21B in the depth direction D. This depth direction D is a direction corresponding to the thickness direction of the positive electrode active material layer 21B as shown in Fig. 2 and Fig. 4. More specifically, the depth direction D is a direction from the surface of the positive electrode active material layer 21B toward the inside of the positive electrode active material layer 21B, that is, a direction from the covering portion 212 toward the center portion 211.

[0127] In this depth analysis, normal ion analysis using primary ions and sputter etching for digging down the positive electrode active material layer 21B using sputter ions are alternately repeated in the depth direction D. This measures the amounts of various ions detected from the positive electrode active material layer 21B in the depth direction D, and thus obtains the analysis results of the depth analysis of the positive electrode active material layer 21B as shown in Figs.

[0128] As described above, the horizontal axis indicates the sputtering time during sputter etching, and therefore corresponds to the position (so-called depth) in the depth direction D inside the positive electrode active material layer 21B. Also, as described above, the vertical axis indicates the ion intensity, and therefore corresponds to the detected amount of various ions in the depth direction D.

[0129] 3 and 4, the positive electrode active material particle 210 includes a core 211 and a coating portion 212, and the coating portion 212 includes an upper coating portion 212A and a lower coating portion 212B. The core 211 also includes a lithium composite oxide, and the lithium composite oxide content is 80 mol % or more. Furthermore, as described above, the upper coating portion 212A includes lithium fluoride, and the lower coating portion 212B includes lithium metaborate.

[0130] [Physical property conditions] In the following, three types of physical property conditions will be described by dividing the cases into a case where the electrolyte does not contain a boron-fluorine-containing material and a case where the electrolyte contains a boron-fluorine-containing material.

[0131] (If the electrolyte does not contain boron-fluorine-containing materials) In the case where the electrolyte does not contain a boron-fluorine-containing material, the details of the first physical property condition, the second physical property condition, and the third physical property condition are as described below.

[0132] (First physical property condition) In a depth analysis of the positive electrode active material layer 21B using TOF-SIMS, LiF2 - The first negative secondary ions originating from are detected.

[0133] 5, a first depth profile 5A is obtained, which represents a change in the ion intensity of the first negative secondary ions in the depth direction D. In the first depth profile 5A, as the sputtering time increases, the detected amount of the first negative secondary ions increases and then decreases, so that the ion intensity of the first negative secondary ions increases and then decreases. As a result, the first depth profile 5A has a first peak P1.

[0134] 5, a vertical line segment (dotted chain line) passing through the first peak P1 represents the position of the first peak P1. The position of the first peak P1 is the sputtering time corresponding to the first peak P1, and therefore is a depth representing the position in the depth direction D.

[0135] The reason why the ion intensity of the first negative secondary ions increases and then decreases in the depth direction D in the first depth profile 5A is as follows.

[0136] As described above, the positive electrode active material layer 21B contains not only a plurality of positive electrode active material particles 210 but also other materials such as a positive electrode binder and a positive electrode conductor. In the positive electrode active material particle 210, a lower covering portion 212B is disposed on the outside of the central portion 211, and an upper covering portion 212A is disposed on the outside of the lower covering portion 212B.

[0137] Upper covering portion 212A contains lithium fluoride, and therefore contains lithium and fluorine as constituent elements. In contrast, other materials do not contain lithium or fluorine as constituent elements. Lower covering portion 212B contains lithium metaborate, and therefore contains lithium as a constituent element but does not contain fluorine as a constituent element. Furthermore, central portion 211 contains a lithium composite oxide, and therefore contains lithium as a constituent element but does not contain fluorine as a constituent element.

[0138] In this case, when the depth of the positive electrode active material layer 21B is analyzed using TOF-SIMS, the analysis range moves in this order toward the region where other materials are present, the region where the upper covering portion 212A is present, the region where the lower covering portion 212B is present, and the region where the central portion 211 is present. As a result, the first negative secondary ions are sufficiently detected in the region where lithium and fluorine are sufficiently present, whereas the first negative secondary ions are hardly detected in the region where almost no lithium and fluorine are present.

[0139] For these reasons, the ionic intensity of the first negative secondary ions decreases in the region where other materials are present, the ionic intensity of the first negative secondary ions increases rapidly in the region where the upper covering portion 212A is present, the ionic intensity of the first negative secondary ions decreases rapidly in the region where the lower covering portion 212B is present, and the intensity of the first negative secondary ions decreases in the region where the central portion 211 is present.

[0140] As a result, the detected amount of the first negative secondary ions increases in the depth direction D and then decreases, so that the ion intensity of the first negative secondary ions increases in the depth direction D and then decreases.

[0141] (Second physical property condition) In a depth analysis of the positive electrode active material layer 21B using TOF-SIMS, BO2 - A second negative secondary ion originating from the

[0142] 5, a second depth profile 5B is obtained which shows the change in the ion intensity of the second negative secondary ions in the depth direction D. In the second depth profile 5B, as the sputtering time increases, the detected amount of the second negative secondary ions increases and then decreases, so that the ion intensity of the second negative secondary ions increases and then decreases. As a result, the second depth profile 5B has a second peak P2.

[0143] 5, a vertical line segment (dotted chain line) passing through the second peak P2 represents the position of the second peak P2. The position of the second peak P2 is the sputtering time corresponding to the second peak P2, and therefore is a depth representing the position in the depth direction D.

[0144] The reason why the ion intensity of the second negative secondary ions immediately increases and then decreases in the depth direction D in the second depth profile 5B is as follows.

[0145] Lower covering portion 212B contains lithium metaborate, and therefore contains boron as a constituent element. In contrast, the other materials do not contain boron as a constituent element. Moreover, upper covering portion 212A contains lithium fluoride, and therefore does not contain boron as a constituent element. Furthermore, central portion 211 contains a lithium composite oxide, and therefore does not contain boron as a constituent element.

[0146] In this case, when the positive electrode active material layer 21B is subjected to depth analysis using TOF-SIMS, the second negative secondary ions are sufficiently detected in the region where boron is sufficiently present, whereas the second negative secondary ions are hardly detected in the region where boron is hardly present.

[0147] For these reasons, the ionic intensity of the second negative secondary ions decreases in the regions where other materials and the upper covering portion 212A are present, the ionic intensity of the second negative secondary ions increases rapidly in the region where the lower covering portion 212B is present, and the ionic intensity of the second negative secondary ions decreases rapidly in the region where the central portion 211 is present.

[0148] As a result, the detected amount of the second negative secondary ions increases in the depth direction D and then decreases, so that the ion intensity of the second negative secondary ions increases in the depth direction D and then decreases.

[0149] (Third physical property condition) As described above, the first depth profile 5A has a first peak P1 and the second depth profile 5B has a second peak P2.

[0150] In this case, the second peak P2 is located deeper than the first peak P1 in the depth direction D. That is, as shown in Fig. 5, in the case where the depth increases toward the right, the second peak P2 is located to the right of the first peak P1.

[0151] The reason why the second peak P2 is located deeper than the first peak P1 in the depth direction D is that, in the vicinity of the surface (coating portion 212) of the positive electrode active material particle 210, the upper covering portion 212A is located farther from the central portion 211 than the lower covering portion 212B, and the lower covering portion 212B is located closer to the central portion 211 than the upper covering portion 212A. In other words, when the covering portion 212 is provided on the surface of the central portion 211, the lower covering portion 212B is arranged outside the central portion 211, and the upper covering portion 212A is arranged outside the lower covering portion 212B.

[0152] As described above, upper covering portion 212A contains lithium and fluorine as constituent elements, and lower covering portion 212B contains lithium, boron and oxygen as constituent elements.

[0153] As a result, as described above, the surface of the central portion 211 is electrochemically and appropriately protected by the covering portion 212. Therefore, even if the central portion 211 contains a lithium composite oxide and the content ratio of the lithium composite oxide is 80 mol % or more, heat generation in the positive electrode 21 is suppressed during overcharging, heating of the secondary battery, and occurrence of an internal short circuit, and therefore a temperature rise in the positive electrode 21 is suppressed.

[0154] (Other physical property conditions) In addition, in the depth analysis of the positive electrode active material layer 21B using TOF-SIMS, as shown in FIG. - Since the third negative secondary ions originating from are detected, a third depth profile 5C is obtained, which represents a change in the ion intensity of the third negative secondary ions in the depth direction D. In the third depth profile 5C, as the sputtering time increases, the ion intensity of the third negative secondary ions increases continuously. As a result, the third depth profile 5C does not have a peak.

[0155] The reason why the ion intensity of the third negative secondary ions continuously increases in the depth direction D in the third depth profile 5C is as follows.

[0156] Since central portion 211 contains a lithium composite oxide, it contains nickel as a constituent element. In contrast, the other materials, upper cover portion 212A and lower cover portion 212B, do not contain nickel as a constituent element.

[0157] In this case, when the positive electrode active material layer 21B is subjected to depth analysis using TOF-SIMS, the third negative secondary ions are sufficiently detected in the area where nickel is sufficiently present, whereas the third negative secondary ions are hardly detected in the area where almost no nickel is present.

[0158] For these reasons, the ionic intensity of the third negative secondary ions decreases in the regions where other materials, upper covering portion 212A and lower covering portion 212B are present, and the ionic intensity of the third negative secondary ions increases in the region where central portion 211 is present.

[0159] As a result, the detected amount of the third negative secondary ions increases continuously in the depth direction D, and therefore the ion intensity of the third negative secondary ions increases continuously in the depth direction D.

[0160] (Composition and properties of positive electrode active material particles for comparison) For comparison, consider a positive electrode active material particle having a configuration similar to that of the positive electrode active material particle 210, except that the covering portion 212 does not include the lower covering portion 212B. This positive electrode active material particle includes the center portion 211 and the covering portion 212 (upper covering portion 212A), and therefore the covering portion 212 does not include the lower covering portion 212B.

[0161] In this case, when the positive electrode active material layer 21B is subjected to depth analysis using TOF-SIMS, the second negative secondary ions are hardly detected, and therefore, in the depth profile showing the change in the ion intensity of the second negative secondary ions in the depth direction D, the ion intensity of the second negative secondary ions hardly changes even if the sputtering time increases. As a result, the depth profile does not have a peak, unlike the second depth profile 5B.

[0162] (If the electrolyte contains boron-fluorine-containing materials) In the case where the electrolyte contains a boron-fluorine-containing material, the details of the first physical property condition, the second physical property condition, and the third physical property condition are as described below.

[0163] (First physical property condition) In a depth analysis of the positive electrode active material layer 21B using TOF-SIMS, LiF2 - The first negative secondary ions originating from are detected.

[0164] As a result, as shown in Fig. 6, a first depth profile 6A is obtained, which represents a change in the ion intensity of the first negative secondary ions in the depth direction D. Since this first depth profile 6A corresponds to the first depth profile 5A shown in Fig. 5, the details of the first depth profile 6A are the same as those of the first depth profile 5A. Therefore, in the first depth profile 6A, for the above-mentioned reason, as the sputtering time increases, the ion intensity of the first negative secondary ions increases and then decreases, so that the first depth profile 6A has a first peak P1.

[0165] (Second physical property condition) In a depth analysis of the positive electrode active material layer 21B using TOF-SIMS, BO2 - A second negative secondary ion originating from the

[0166] As a result, as shown in Fig. 6, a second depth profile 6B is obtained which represents a change in the ion intensity of the second negative secondary ions in the depth direction D. Since this second depth profile 6B corresponds to the second depth profile 5B shown in Fig. 5, the details of the second depth profile 6B are the same as those of the second depth profile 5B. Therefore, in the second depth profile 6B, for the above-mentioned reason, as the sputtering time increases, the ion intensity of the second negative secondary ions increases and then decreases, so that the second depth profile 6B has a second peak P2.

[0167] However, when the electrolyte contains a boron-fluorine containing material, the electrolyte impregnates the positive electrode 21, and boron contained as a constituent element in the boron-fluorine containing material adheres to the surfaces of the positive electrode active material particles 210.

[0168] In this case, the ionic strength of the second negative secondary ions increases locally near the surface of the positive electrode active material particles 210. As a result, in the second depth profile 6B, the ionic strength of the second negative secondary ions immediately decreases in the depth direction D, then increases in the depth direction D, and then decreases. The reason why the ionic strength of the second negative secondary ions increases in the depth direction D and then decreases in the second depth profile 6B is as described above.

[0169] (Third physical property condition) As described above, the first depth profile 6A has the first peak P1, and the second depth profile 6B has the second peak P2. In this case, as described above, the second peak P2 is located deeper than the first peak P1 in the depth direction D. The reason why the second peak P2 is located deeper than the first peak P1 in the depth direction D is as described above.

[0170] As a result, as described above, the surface of the central portion 211 is electrochemically and appropriately protected by the covering portion 212. Therefore, even if the central portion 211 contains a lithium composite oxide and the content ratio of the lithium composite oxide is 80 mol % or more, heat generation in the positive electrode 21 is suppressed during overcharging, heating of the secondary battery, and occurrence of an internal short circuit, and therefore a temperature rise in the positive electrode 21 is suppressed.

[0171] (Other physical property conditions) In addition, in the depth analysis of the positive electrode active material layer 21B using TOF-SIMS, as shown in FIG. -Since the third negative secondary ions originating from are detected, a third depth profile 6C is obtained that represents a change in the ion intensity of the third negative secondary ions in the depth direction D. Since this third depth profile 6C corresponds to the third depth profile 5C shown in FIG. 5, the details of the third depth profile 6C are almost the same as the details of the third depth profile 5C. Therefore, in the third depth profile 6C, for the above-mentioned reason, the ion intensity of the third negative secondary ions increases continuously as the sputtering time increases, so that the third depth profile 6C does not have a peak.

[0172] [Analysis Procedure] The TOF-SIMS analyzer TOF-SIMS V manufactured by ION-TOF can be used as the TOF-SIMS analyzer. The analysis conditions are as follows: Primary ion = Bi 3+ , ion gun acceleration voltage = 25 keV, analysis mode = depth profile analysis using High Current Bunched, irradiated ion current (measured with pulsed beam) = 0.2 pA, pulse frequency = 10 kHz, mass range = 1 amu to 800 amu, scanning range = 200 μm × 200 μm, sputtered ions = Ar + The acceleration voltage of the sputter ion gun is 1 kV, the emission current is 200 mA, and the sputter area is 500 μm×500 μm.

[0173] The procedure for confirming whether or not the three physical property conditions are satisfied by performing a depth analysis of the positive electrode active material layer 21B using TOF-SIMS is as follows.

[0174] First, the secondary battery is discharged in the atmosphere until the voltage reaches 2.0 V. The current during discharge is not particularly limited and can be set arbitrarily.

[0175] Next, the secondary battery is disassembled in a glove box to recover the positive electrode 21, and then the positive electrode 21 is washed with a washing solvent. This removes the electrolyte impregnated in the positive electrode 21. The type of the washing solvent is not particularly limited, but specifically, any one or more types of organic solvents such as dimethyl carbonate are used.

[0176] Next, the cleaned positive electrode 21 is attached to a sample holder using an adhesive tape. The type of adhesive tape is not particularly limited, but specifically, it is a carbon tape, etc. Next, the positive electrode active material layer 21B is subjected to depth analysis using TOF-SIMS to obtain the analysis results shown in FIG. 5 or FIG. 6.

[0177] Finally, based on the analysis results shown in FIG. 5 or FIG. 6, it is confirmed whether the three physical property conditions are satisfied.

[0178] Specifically, when the first negative secondary ions are detected and the first depth profile 5A having the first peak P1 is acquired, the first physical property condition is satisfied. On the other hand, when the first negative secondary ions are not detected, or when the first negative secondary ions are detected but the first depth profile 5A having the first peak P1 is not acquired, the first physical property condition is not satisfied.

[0179] In addition, if the second negative secondary ions are detected and therefore the second depth profile 5B having the second peak P2 is acquired, the second physical property condition is satisfied. In contrast, if the second negative secondary ions are not detected, or if the second negative secondary ions are detected but the second depth profile 5B having the second peak P2 is not acquired, the second physical property condition is not satisfied.

[0180] Furthermore, the third physical property condition is satisfied when the second peak P2 is located deeper than the first peak P1 in the depth direction D. On the other hand, when the second peak P2 is not located deeper than the first peak P1 in the depth direction D, the third physical property condition is not satisfied.

[0181] [Reasons for using TOF-SIMS as an analytical method] The reason for using TOF-SIMS (depth analysis) as the analysis method for investigating the physical properties of the positive electrode 21 is as follows.

[0182] First, the thickness of covering portion 212 (upper covering portion 212A and lower covering portion 212B) is assumed to be extremely thin, being approximately several nm. In this case, in order to analyze positive electrode active material layer 21B in depth direction D, it is effective to employ TOF-SIMS (depth analysis) which has extremely high depth resolution.

[0183] Secondly, when multiple types of compounds are present inside the positive electrode active material layer 21B, it is more effective to use TOF-SIMS, which can examine the compositions of the multiple types of compounds individually, rather than using an analytical method that can examine the average composition of the positive electrode active material layer 21B.

[0184] In particular, in general, when investigating the composition of a coating, analytical methods such as X-ray photoelectron spectroscopy (XPS) and transmission electron energy loss spectroscopy (TEM-EELS) are used.

[0185] However, in XPS, the spectrum derived from boron and the spectrum derived from phosphorus overlap each other, making it difficult to examine the chemical bonding state of the boron, and even to examine the presence or absence of boron.

[0186] In addition, in TEM-EELS (particle cross-sectional analysis), when a line analysis is performed on a coating in the depth direction D, the average composition containing lithium, boron, and oxygen is analyzed in a state in which not only lithium metaborate but also other compounds are included, making it difficult to analyze only the lithium metaborate.

[0187] In contrast, TOF-SIMS analyzes only the lithium metaborate for its average composition containing lithium, boron and oxygen, making it possible to analyze only the lithium metaborate.

[0188] Third, while surface analysis using TOF-SIMS makes it possible to analyze the various ions present on the surface of a coating, it is difficult to analyze the various ions present inside the coating.

[0189] In contrast, in the depth analysis using TOF-SIMS, it is possible to analyze not only various ions present on the surface of the coating, but also various ions present inside the coating. This makes it possible to analyze various ions present inside the positive electrode active material layer 21B, and more specifically, it is possible to analyze various ions present inside the coating portion 212 (upper coating portion 212A and lower coating portion 212B) provided on the surface of the center portion 211.

[0190] <1-4. Operation> This secondary battery operates in the battery element 20 as follows.

[0191] During charging, lithium is released from the positive electrode 21 and is absorbed in the negative electrode 22 via the electrolyte. During discharging, lithium is released from the negative electrode 22 and is absorbed in the positive electrode 21 via the electrolyte. During discharging and charging, lithium is absorbed and released in an ionic state.

[0192] <1-5. Manufacturing method> FIG. 7 shows a cross-sectional configuration corresponding to FIG. 4 for explaining a method for manufacturing a secondary battery.

[0193] When manufacturing a secondary battery, the positive electrode 21 and the negative electrode 22 are produced and an electrolytic solution is prepared using the procedure described below as an example. The positive electrode 21, the negative electrode 22, and the electrolytic solution are then used to assemble a secondary battery, and a stabilization process is performed on the assembled secondary battery.

[0194] In the following, a case will be described in which upper covering portion 212A contains lithium fluoride and lower covering portion 212B contains lithium metaborate.

[0195] [Preparation of positive electrode] First, a plurality of cores 211 containing a lithium composite oxide are prepared. As described above, the content of the lithium composite oxide is 80 mol % or more.

[0196] Next, a powdered boron-oxygen containing material is supplied onto the surface of each of the multiple central parts 211. This boron-oxygen containing material is a material containing boron and oxygen as constituent elements, and is a material for forming lower covering portion 212B. As described above, in order to form lower covering portion 212B containing lithium metaborate, powdered lithium metaborate containing lithium as a constituent element together with boron and oxygen is used as the boron containing material.

[0197] As a result, the powdered boron-oxygen-containing material is fixed on the surface of each of the multiple central parts 211, so that the surface of each of the multiple central parts 211 is dry-coated with the powdered boron-oxygen-containing material. Thus, as shown in FIG. 7, a lower coating portion 212B containing the boron-oxygen-containing material is formed on the surface of each of the multiple central parts 211.

[0198] In this case, the surface of each of the multiple central parts 211 may be dry-coated with the boron-oxygen-containing material, and then the multiple central parts 211 may be fired. This is because the boron-oxygen-containing material is more likely to diffuse uniformly on the surface of the central part 211, and the fixation of the boron-oxygen-containing material to the surface of the central part 211 is improved. The firing temperature is not particularly limited, but is specifically 300°C to 500°C.

[0199] Next, a powdered carbon-oxygen containing material is supplied to the surface of each of the multiple central parts 211 on which the lower covering portion 212B has been formed. This carbon-oxygen containing material is a material containing carbon and oxygen as constituent elements, and is a material for forming the precursor covering portion 212Z, which will be described later, formed before the formation of the upper covering portion 212A. Here, as described above, in order to form the upper covering portion 212A containing lithium fluoride, powdered lithium carbonate (Li2CO3) containing lithium as a constituent element together with carbon and oxygen is used as the carbon-oxygen containing material.

[0200] As a result, the powdered carbon-oxygen containing material is fixed on the surface of the lower covering portion 212B, and the surface of the lower covering portion 212B is dry-coated with the powdered carbon-oxygen containing material. Thus, as shown in Fig. 7, a precursor covering portion 212Z containing the carbon-oxygen containing material is formed on the surface of the lower covering portion 212B. This precursor covering portion 212Z is ​​a preparatory layer used for forming the upper covering portion 212A by utilizing a stabilization process for the assembled secondary battery, which will be described later.

[0201] In this case, the surface of the lower covering portion 212B may be dry-coated with the carbon-oxygen-containing material, and then the lower covering portion 212B may be baked. This is because the carbon-oxygen-containing material is more likely to diffuse uniformly on the surface of the lower covering portion 212B, and the fixation of the carbon-oxygen-containing material to the surface of the lower covering portion 212B is improved. The baking temperature is not particularly limited, but is typically about 300°C.

[0202] As described above, the firing temperature of lower covering portion 212B is preferably lower than the firing temperature of multiple central portions 211. This is to prevent the constituent materials of lower covering portion 212B and upper covering portion 212A from unintentionally excessively diffusing into each other when upper covering portion 212A is formed on lower covering portion 212B in a process described later.

[0203] As a result, as shown in FIG. 7, a plurality of precursor particles 210Z including a central portion 211, a lower coating portion 212B and a precursor coating portion 212Z are formed.

[0204] Next, the plurality of precursor particles 210Z, the positive electrode binder, and the positive electrode conductive agent are mixed together to prepare a positive electrode mixture. Next, the positive electrode mixture is poured into a solvent to prepare a paste-like positive electrode mixture slurry. This solvent may be an aqueous solvent or an organic solvent.

[0205] Next, a precursor layer (not shown) is formed by applying the positive electrode mixture slurry to both sides of the positive electrode current collector 21A. This precursor layer includes a precursor coating portion 212Z instead of the upper coating portion 212A, and therefore has a configuration similar to that of the positive electrode active material layer 21B, except that the coating portion 212 is not yet provided on the surfaces of the multiple central portions 211. After this, the precursor layer may be compression molded using a compression device such as a roll press. In this case, the precursor layer may be heated, or compression molding may be repeated multiple times.

[0206] Next, the positive electrode current collector 21A on which the precursor layer is formed is stored in a humid environment. For the humid environment, an environmental tester capable of adjusting humidity is used. The storage conditions such as humidity and storage time are not particularly limited and can be set arbitrarily.

[0207] As a result, moisture (HO) adheres to the surface of the precursor layer. The amount of moisture adhered can be set arbitrarily depending on the storage conditions described above.

[0208] The reason why moisture is attached to the surface of the precursor layer is to convert the precursor coating portion 212Z into the upper coating portion 212A by utilizing a reaction between the moisture and the precursor coating portion 212Z (carbon-oxygen containing material), as will be described later.

[0209] Finally, as described later, after assembling the secondary battery, a stabilization process is carried out using the assembled secondary battery.

[0210] In this stabilization treatment, the moisture adhering to the surface of the precursor layer reacts with the carbon-oxygen-containing material, converting the precursor coating portion 212Z into an upper coating portion 212A. As a result, coating portions 212 including upper coating portions 212A and lower coating portions 212B are formed on the surfaces of the respective central portions 211, converting the plurality of precursor particles 210Z into a plurality of positive electrode active material particles 210. Thus, a positive electrode active material layer 21B including the plurality of positive electrode active material particles 210 is formed, and the positive electrode 21 is produced.

[0211] The reaction by which the precursor coating portion 212Z is ​​converted into the upper coating portion 212A will be described in detail later.

[0212] When producing this positive electrode 21, the amount of each of upper covering portion 212A and lower covering portion 212B formed can be adjusted.

[0213] Specifically, the amount of upper covering portion 212A formed varies depending on the dry coating amount of the carbon-oxygen containing material, which makes it possible to adjust the thickness of upper covering portion 212A and the content of upper covering portion 212A in positive electrode active material particle 210.

[0214] Furthermore, since the amount of moisture adhering to the surface of the precursor layer changes depending on the storage conditions in a humid environment, the amount of upper covering portion 212A formed changes. This makes it possible to adjust the thickness of upper covering portion 212A and the content of upper covering portion 212A in positive electrode active material particle 210.

[0215] Furthermore, the amount of the lower coating portion 212B formed varies depending on the dry coating amount of the boron oxygen content, which makes it possible to adjust the thickness of the lower coating portion 212B and the content of the lower coating portion 212B in the positive electrode active material particles 210.

[0216] [Preparation of negative electrode] First, the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent are mixed together to prepare a negative electrode mixture. Then, the negative electrode mixture is poured into a solvent to prepare a paste-like negative electrode mixture slurry. Details regarding the solvent are as described above. Finally, the negative electrode mixture slurry is applied to both sides of the negative electrode current collector 22A to form the negative electrode active material layer 22B. After this, the negative electrode active material layer 22B may be compression molded using a compression device such as a roll press. In this case, the negative electrode active material layer 22B may be heated, or the compression molding may be repeated multiple times. In this way, the negative electrode 22 is produced.

[0217] [Preparation of electrolyte] The electrolyte salt is added to the solvent. As a result, the electrolyte salt is dispersed or dissolved in the solvent, and thus an electrolyte solution is prepared. In this case, a boron-fluorine-containing material may be added to the electrolyte solution as necessary.

[0218] [Secondary battery assembly] First, the positive electrode lead 31 is connected to the positive electrode current collector 21A of the positive electrode 21 using a joining method such as welding, and the negative electrode lead 32 is connected to the negative electrode current collector 22A of the negative electrode 22 using a joining method such as welding.

[0219] Next, the positive electrode current collector 21A on which the precursor layer has been formed and the negative electrode 22 are stacked together with the separator 23 interposed therebetween to form a laminate (not shown). Next, the laminate is wound to produce a wound body (not shown), and then the wound body is pressed using a compression device such as a press machine to form the wound body into a flat shape. The wound body after this formation has a similar configuration to that of the battery element 20, except that it contains the precursor layer instead of the positive electrode active material layer 21B and is not impregnated with an electrolyte solution.

[0220] Next, after the roll is accommodated in the recess 10U, the exterior film 10 (adhesive layer / metal layer / surface protection layer) is folded to face the exterior films 10. Next, the outer peripheral edges of two sides of the opposing adhesive layers are bonded to each other using an adhesion method such as a heat fusion method, thereby accommodating the roll in the bag-shaped exterior film 10.

[0221] Finally, after injecting an electrolyte solution into the bag-shaped exterior film 10, the outer peripheral edges of the remaining sides of the opposing fusion layers are bonded to each other using a bonding method such as a heat fusion method. In this case, a sealing film 41 is inserted between the exterior film 10 and the positive electrode lead 31, and a sealing film 42 is inserted between the exterior film 10 and the negative electrode lead 32.

[0222] As a result, the wound body is impregnated with the electrolyte and is enclosed inside the bag-shaped exterior film 10, thereby assembling a secondary battery.

[0223] [Stabilization of secondary batteries after assembly] Here, the procedure of the stabilization treatment will be described, and then the reaction by which the precursor coating portion 212Z is ​​converted into the upper coating portion 212A will be described.

[0224] (Stabilization procedure) First, the assembled secondary battery is charged in a normal temperature and humidity environment. The charging conditions can be set arbitrarily. The temperature of the environment is not particularly limited, but specifically, it is 10°C to 35°C, and the humidity of the environment is not particularly limited, but specifically, it is 10% to 60%.

[0225] Next, the assembled secondary battery in a charged state is stored in a high-temperature environment. The environmental temperature is not particularly limited, but specifically, it is 50° C. to 90° C., and the storage time is not particularly limited, but specifically, it is 3 hours to 48 hours.

[0226] Finally, the assembled secondary battery in a charged state is discharged in a normal temperature and humidity environment. The discharge conditions can be set arbitrarily. The details of the temperature and humidity of the environment are as described above.

[0227] Thereby, as described above, the precursor coating portion 212Z is ​​converted into the upper coating portion 212A, and therefore the plurality of precursor particles 210Z is converted into the plurality of positive electrode active material particles 210. In this case, the coating portion 212 including the upper coating portion 212A and the lower coating portion 212B is formed on the surface of each of the plurality of central portions 211, and therefore the plurality of positive electrode active material particles 210 is formed. Thus, the positive electrode active material layer 21B including the plurality of positive electrode active material particles 210 is formed, and the positive electrode 21 is produced.

[0228] Furthermore, since a coating is formed on the surface of the positive electrode 21, the positive electrode 21 is electrochemically stabilized, and since a coating is formed on the surface of the negative electrode 22, the negative electrode 22 is electrochemically stabilized.

[0229] From these steps, a battery element 20 including a positive electrode 21, a negative electrode 22, and an electrolyte is produced, and the battery element 20 is sealed in a bag-shaped exterior film 10, completing a secondary battery.

[0230] (The reaction in which the precursor coating part is converted into the upper coating part) In the stabilization treatment, the precursor coating portion 212Z is ​​converted into the upper coating portion 212A by utilizing the reaction described below.

[0231] In the following, a case where the fluorine-containing lithium salt contained in the electrolyte is lithium hexafluorophosphate will be described, and a case where the electrolyte contains a boron-fluorine-containing material, and the boron-fluorine-containing material is lithium tetrafluoroborate will be described.

[0232] As described above, before the stabilization treatment, the precursor coating portion 212Z containing a carbon-oxygen-containing material (lithium carbonate) is formed on the surface of the lower coating portion 212B.

[0233] In the stabilization treatment, when the assembled secondary battery is stored in a high-temperature environment, the moisture present near the surface of the precursor coating portion 212Z reacts with the fluorine-containing lithium salt contained in the electrolyte, causing the reaction represented by formula (11) to proceed. This reaction is more likely to proceed near the surface of the precursor coating portion 212Z where a large amount of moisture is present.

[0234] H2O+LiPF6→LiF+2HF+POF3...(11)

[0235] As a result, hydrogen fluoride (HF) is formed by utilizing the reaction between moisture and the fluorine-containing lithium salt, and the concentration of hydrogen fluoride in the electrolyte increases. In other words, the fluorine-containing lithium salt becomes a source of hydrogen fluoride.

[0236] When the concentration of hydrogen fluoride in the electrolyte increases, the carbon-oxygen containing material (Li2CO3) contained in the precursor coating portion 212Z reacts with hydrogen fluoride, and the reaction represented by formula (12) proceeds.

[0237] Li2CO3+2HF→2LiF+CO2+H2O ···(12)

[0238] As a result, lithium fluoride (LiF) is formed by utilizing the reaction between the carbon-oxygen-containing material and hydrogen fluoride, and the carbon-oxygen-containing material is converted into lithium fluoride, and thus upper covering portion 212A containing lithium fluoride is formed, and precursor covering portion 212Z is ​​converted into upper covering portion 212A.

[0239] In this case, if the electrolyte contains a boron-fluorine-containing material, the reaction represented by formula (13) proceeds. That is, the boron-fluorine-containing material, like the fluorine-containing lithium salt, serves as a source of hydrogen fluoride.

[0240] 2LiBF4+3H2O→2LiF+B2O3+6HF ···(13)

[0241] This allows hydrogen fluoride to be formed by utilizing the reaction between the boron-fluorine containing material and moisture, facilitating the reaction shown in formula (12), and thus facilitating the conversion of the precursor coating portion 212Z to the upper coating portion 212A.

[0242] <1-6. Actions and Effects> According to this secondary battery, the positive electrode active material layer 21B of the positive electrode 21 contains a plurality of positive electrode active material particles 210, the positive electrode active material particles 210 including a central portion 211 and a coating portion 212, the central portion 211 including a lithium composite oxide, the lithium composite oxide having a layered rock-salt type crystal structure and including lithium, nickel and other elements as constituent elements, the lithium composite oxide content being 80 mol % or more, the coating portion 212 including lithium, fluorine, boron and oxygen as constituent elements, and the electrolyte salt of the electrolyte solution including a fluorine-containing lithium salt.

[0243] In addition, three types of physical property conditions are satisfied with respect to the physical properties of the positive electrode 21. Specifically, in a depth analysis of the positive electrode active material layer 21B using TOF-SIMS, - The first negative secondary ions and BO2 -A second negative secondary ion derived from the first negative secondary ion is detected, and a second peak P2 in the change in ion intensity of the second negative secondary ion is located deeper in the depth direction D than a first peak P1 in the change in ion intensity of the first negative secondary ion.

[0244] In this case, since the core portion 211 contains a lithium composite oxide and the content of the lithium composite oxide is 80 mol or more, the potential for absorbing and releasing lithium decreases as described above, thereby obtaining a high battery capacity.

[0245] Moreover, since the three types of physical property conditions are satisfied with respect to the physical properties of the positive electrode 21, the surface of the center portion 211 is electrochemically and appropriately protected by the covering portion 212 as described above. This prevents the positive electrode 21 from generating heat during overcharging, when the secondary battery is heated, when an internal short circuit occurs, and the like, even if the content of the lithium composite oxide is 80 mol % or more. This prevents the temperature rise of the positive electrode 21 even if the secondary battery becomes in an unsafe state, making it less likely for the secondary battery to malfunction, such as ignition.

[0246] For these reasons, the battery capacity is guaranteed by the central portion 211, while the covering portion 212 suppresses an excessive temperature rise in the positive electrode 21 even during overcharging, heating of the secondary battery, and occurrence of an internal short circuit. Therefore, excellent safety can be obtained while the battery characteristics are guaranteed.

[0247] In particular, if covering portion 212 includes upper covering portion 212A and lower covering portion 212B in this order from the side farthest from center portion 211, upper covering portion 212A including lithium and fluorine as constituent elements, and lower covering portion 212B including lithium, boron, and oxygen as constituent elements, the three types of physical property conditions are more likely to be satisfied with respect to the physical properties of positive electrode 21. Therefore, the surface of center portion 211 is more likely to be electrochemically protected by covering portion 212, and a greater effect can be obtained.

[0248] In this case, if upper covering portion 212A contains lithium fluoride and lower covering portion 212B contains lithium metaborate, the surface of central portion 211 is sufficiently electrochemically protected by covering portion 212, thereby achieving even greater effectiveness.

[0249] Furthermore, if the lithium composite oxide contains one or more of the following other elements: cobalt, aluminum, manganese, zirconium, titanium, molybdenum, tantalum, chromium, niobium, iron, copper, zinc, vanadium, magnesium, tungsten, sulfur, strontium, boron, sodium, and fluorine, a sufficient battery capacity can be obtained, thereby achieving a greater effect.

[0250] Furthermore, if the fluorine-containing lithium salt contains one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the precursor coating portion 212Z can be easily converted into the upper coating portion 212A by using the fluorine-containing lithium salt, thereby achieving a greater effect.

[0251] Furthermore, if the electrolyte further contains a boron-fluorine containing material, the precursor coating portion 212Z can be easily converted into the upper coating portion 212A by utilizing the boron-fluorine containing material, and therefore a greater effect can be obtained.

[0252] In this case, if the boron-fluorine-containing material contains one or both of lithium tetrafluoroborate and lithium difluoro(oxalato)borate, the precursor coating portion 212Z can be sufficiently converted into the upper coating portion 212A by utilizing the boron-fluorine-containing material, thereby obtaining an even greater effect.

[0253] Furthermore, if the secondary battery is a lithium ion secondary battery, a sufficient battery capacity can be stably obtained by utilizing the absorption and release of lithium, so that a higher effect can be obtained.

[0254] <2. Modifications> Next, modified examples of the above-mentioned secondary battery will be described. The configuration of the secondary battery can be modified as appropriate, as described below. However, the series of modified examples described below may be combined with each other.

[0255] [Variation 1] A porous membrane separator 23 was used. However, although not specifically shown here, a laminated separator may be used instead of the porous membrane separator 23.

[0256] Specifically, the laminated separator includes a porous film and a polymer compound layer. The porous film has a pair of surfaces, and the polymer compound layer is provided on one or both surfaces of the porous film. This is because the adhesiveness of the separator to each of the positive electrode 21 and the negative electrode 22 is improved, and thus the positional deviation of the battery element 20 is suppressed. This suppresses the winding deviation of each of the positive electrode 21, the negative electrode 22, and the separator, and thus suppresses the swelling of the secondary battery even if a decomposition reaction of the electrolyte occurs. The polymer compound layer includes a polymer compound such as polyvinylidene fluoride. Polyvinylidene fluoride has excellent physical strength and is electrochemically stable.

[0257] One or both of the porous film and the polymer compound layer may contain one or more of a plurality of insulating particles. This is because the plurality of insulating particles dissipate heat when the secondary battery generates heat, improving the safety (heat resistance) of the secondary battery. The plurality of insulating particles contain one or more of insulating materials such as inorganic materials and resin materials. Specific examples of inorganic materials include aluminum oxide, aluminum nitride, boehmite, silicon oxide, titanium oxide, magnesium oxide, and zirconium oxide. Specific examples of resin materials include acrylic resin and styrene resin.

[0258] In the case of producing a laminated separator, a precursor solution containing a polymer compound and an organic solvent is prepared, and then the precursor solution is applied to one or both sides of a porous film. In this case, the precursor solution may contain a plurality of insulating particles.

[0259] Even when this laminated separator is used, the same effect can be obtained because lithium can move in an ionic state between the positive electrode 21 and the negative electrode 22. In this case, as described above, in particular, swelling of the secondary battery is suppressed, and therefore a higher effect can be obtained.

[0260] [Variation 2] An electrolyte solution that is a liquid electrolyte is used, but an electrolyte layer that is a gel electrolyte may also be used, although this is not specifically shown.

[0261] In the battery element 20 using the electrolyte layer, the positive electrode 21 and the negative electrode 22 are wound facing each other with the separator 23 and the electrolyte layer interposed therebetween. The electrolyte layer is interposed between the positive electrode 21 and the separator 23, and is also interposed between the negative electrode 22 and the separator 23.

[0262] Specifically, the electrolyte layer contains a polymer compound together with an electrolyte solution, and the electrolyte solution is held by the polymer compound. This is because leakage of the electrolyte solution is prevented. The composition of the electrolyte solution is as described above. The polymer compound contains polyvinylidene fluoride and the like. When forming the electrolyte layer, a precursor solution containing an electrolyte solution, a polymer compound, and a solvent is prepared, and then the precursor solution is applied to one or both sides of the positive electrode 21 and the precursor solution is applied to one or both sides of the negative electrode 22.

[0263] Even when this electrolyte layer is used, the same effect can be obtained because lithium can move in an ionic state between the positive electrode 21 and the negative electrode 22 via the electrolyte layer. In this case, leakage of the electrolyte is particularly prevented as described above, so that a higher effect can be obtained. EXAMPLES

[0264] An embodiment of the present technology will be described.

[0265] <Examples 1 and 2 and Comparative Examples 1 to 4> As described below, a secondary battery was fabricated, and then the battery characteristics of the secondary battery were evaluated. Here, in order to simply evaluate the battery characteristics, a test secondary battery described later was fabricated, and then the battery characteristics were evaluated using the test secondary battery.

[0266] [Preparation of secondary battery] In the following, the configuration of the test secondary battery will be briefly described, and then the procedure for fabricating the test secondary battery will be described.

[0267] (Structure of secondary battery) FIG. 8 shows a cross-sectional structure of a test secondary battery, which is a so-called coin-type lithium-ion secondary battery.

[0268] As shown in FIG. 8, this secondary battery includes a test electrode 61, a counter electrode 62, a separator 63, an exterior cup 64, an exterior can 65, a gasket 66, and an electrolyte (not shown).

[0269] The test electrode 61 is housed in an exterior cup 64, and the counter electrode 62 is housed in an exterior can 65. The test electrode 61 and the counter electrode 62 are stacked together with a separator 63 interposed therebetween, and the test electrode 61, the counter electrode 62, and the separator 63 are each impregnated with an electrolyte. The exterior cup 64 and the exterior can 65 are crimped together with a gasket 66, so that the test electrode 61, the counter electrode 62, and the separator 63 are sealed inside the exterior cup 64 and the exterior can 65.

[0270] (Secondary battery manufacturing procedure) The secondary battery shown in FIG. 8 was fabricated according to the procedure described below.

[0271] (Preparation of test pole) First, several cores (lithium composite oxides) were prepared. The lithium composite oxides were LiNi 0.86 Co 0.10 Mn 0.04 O2(LNCM) and LiNi 0.88 Co 0.10 Al 0.02 O2(LNCA) was used. The content (mol%) of the lithium composite oxide is as shown in Table 1.

[0272] Next, a powdered boron-oxygen-containing material (powdered lithium metaborate) was supplied to the surface of each of the multiple cores. As a result, the surface of each of the multiple cores was dry-coated with the powdered boron-oxygen-containing material, forming a lower coating portion containing the boron-oxygen-containing material. In this case, the content (wt%) of the lower coating portion in the positive electrode active material particles was set as shown in Table 1.

[0273] Next, a powdered carbon-oxygen-containing material (powdered lithium carbonate) was supplied to the surface of each of the multiple cores on which the lower coating portion was formed. As a result, the surface of the lower coating portion was dry-coated with the powdered carbon-oxygen-containing material, and a precursor coating portion containing the carbon-oxygen-containing material was formed. Thus, multiple precursor particles including a core, a lower coating portion, and a precursor coating portion were formed.

[0274] Next, 95.5 parts by mass of the precursor particles, 2.5 parts by mass of a positive electrode binder (polyvinylidene fluoride), 1.9 parts by mass of a positive electrode conductive agent (carbon black), and 0.1 parts by mass of a dispersant (polyvinylpyrrolidone) were mixed together to prepare a positive electrode mixture. Next, the positive electrode mixture was added to a solvent (N-methyl-2-pyrrolidone, an organic solvent), and the solvent was stirred to prepare a paste-like positive electrode mixture slurry.

[0275] Next, the positive electrode mixture slurry was applied to one side of a positive electrode current collector (aluminum foil, thickness = 15 μm), and then the positive electrode mixture slurry was dried (drying temperature = 100 °C, drying time = 15 minutes) to form a precursor layer (thickness = 50 μm).

[0276] Next, the positive electrode current collector on which the precursor layer was formed was stored (storage time: 30 minutes) in a humidified environment (temperature = 30 °C, humidity = 50%) using an environmental tester, which caused moisture to adhere to the surface of the precursor layer.

[0277] Next, the positive electrode current collector on which the precursor layer was formed was punched out into a disk shape (diameter = 16.5 mm).

[0278] Finally, as described below, a secondary battery was assembled using the positive electrode current collector on which the precursor layer was formed, and the assembled secondary battery was then subjected to a stabilization treatment. As a result, lithium carbonate was converted to lithium fluoride using the reactions shown in formulas (11) and (12), and the precursor coating portion was converted to an upper coating portion. In this case, the content (wt%) of the upper coating portion in the positive electrode active material particles was set as shown in Table 1.

[0279] Thus, a coating portion including a lower coating portion and an upper coating portion was formed on each surface of the plurality of central portions, and thus the plurality of precursor particles were converted into a plurality of positive electrode active material particles. As a result, a plurality of positive electrode active material particles including the central portions and coating portions were formed, and thus a positive electrode active material layer including the plurality of positive electrode active material particles was formed. Thus, the test electrode 61 was produced.

[0280] When producing this test electrode 61, the composition of the positive electrode active material particles was changed using the procedure described below.

[0281] First, the content (wt%) of the lower coating portion in the positive electrode active material particles was adjusted by changing the amount of boron-oxygen-containing material supplied to the surface of the core portion, which changed the amount of boron-oxygen-containing material attached to the surface of the core portion, and therefore the thickness of the lower coating portion.

[0282] Secondly, the content (wt%) of the upper coating part in the positive electrode active material particles was adjusted by changing the amount of the carbon-oxygen-containing material supplied to the surface of the lower coating part, which changed the amount of the carbon-oxygen-containing material attached to the surface of the center part, and therefore the thickness of the upper coating part.

[0283] Thirdly, the content (wt%) of the upper coating portion in the positive active material particles was adjusted by changing the storage conditions (humidity and storage time) when the positive current collector on which the precursor layer was formed was stored in a humid environment. As a result, the amount of moisture attached to the surface of the precursor layer changed, and the progress of the reactions shown in formulas (11) and (12) changed, and therefore the thickness of the upper coating portion changed.

[0284] (Preparation of counter electrode) A lithium metal plate was punched out into a disk shape (diameter = 17 mm), thereby producing a counter electrode 62.

[0285] (Preparation of electrolyte) An electrolyte salt (lithium hexafluorophosphate, a fluorine-containing lithium salt) was added to a solvent (ethylene carbonate, a cyclic carbonate ester, and dimethyl carbonate, a chain carbonate ester), and the solvent was then stirred. The mixing ratio (weight ratio) of the solvent was ethylene carbonate:dimethyl carbonate = 30:70. The content of the electrolyte salt in the solvent was 1.4 mol / l (=1 mol / dm 3 ) Thus, the electrolyte solution was prepared.

[0286] (Assembling the secondary battery after assembly) First, the positive electrode current collector on which the precursor layer was formed was housed in an exterior cup 64, and the counter electrode 62 was housed in an exterior can 65. Next, the positive electrode current collector on which the precursor layer was formed and the counter electrode 62 were laminated together via a separator 63 (a disk-shaped polyethylene film having a diameter of 17.5 μm) impregnated with an electrolytic solution. In this case, the precursor layer and the counter electrode 62 were made to face each other via the separator 63.

[0287] Next, in a state in which the positive electrode current collector on which the precursor layer was formed and the counter electrode 62 were stacked together with the separator 63 interposed therebetween, the exterior cup 64 and the exterior can 65 were crimped together with the gasket 66. As a result, the positive electrode current collector on which the precursor layer was formed and the counter electrode 62 were enclosed inside the test electrode 61 and the counter electrode 62, and a secondary battery was assembled.

[0288] Finally, the assembled secondary battery was left to stand (standing time=10 hours), whereby a part of the electrolyte impregnated in separator 63 permeated into test electrode 61.

[0289] (Stabilization of secondary batteries after assembly) First, the assembled secondary battery was charged in the air (temperature = 23°C, humidity = 30%), which is a normal temperature and humidity environment. In this case, it was charged at a constant current of 0.1C until the voltage reached 4.45V, and then it was charged at a constant voltage of 4.45V until the current reached 0.01C. Note that 0.1C is the current value at which the battery capacity (theoretical capacity) is fully discharged in 10 hours, and 0.01C is the current value at which the battery capacity is fully discharged in 100 hours.

[0290] Next, the assembled secondary battery in a charged state was stored (storage time=24 hours) in a high-temperature environment, that is, in an oven (temperature=60° C.).

[0291] As a result, as described above, a coating portion including a lower coating portion and an upper coating portion was formed on the surface of each of the plurality of central portions, thereby forming a plurality of positive electrode active material particles, and thus a positive electrode active material layer including a plurality of positive electrode active material particles was formed, thereby producing a test electrode 61.

[0292] Finally, the assembled secondary battery in a charged state was discharged in the air, which is an environment of normal temperature and humidity. In this case, the battery was discharged at a constant current of 0.1 C until the voltage reached 2.50 V.

[0293] In this way, the secondary battery was completed (Examples 1 and 2).

[0294] [Preparation of a secondary battery for comparison] For comparison, other secondary batteries were also fabricated using the procedure described below.

[0295] First, a secondary battery was produced in the same manner except that a covering portion including only an upper covering portion was formed instead of forming a lower covering portion (Comparative Examples 1 and 2).

[0296] Secondly, as described below, a secondary battery was produced by the same procedure as described in the above-mentioned Patent Document 1 (JP Patent Publication No. 2022-525463), except that multiple positive electrode active material particles were formed using the procedure disclosed therein (Comparative Example 3).

[0297] When forming multiple positive electrode active material particles, first, 120 parts by mass of multiple cores (LNCM) and 100 parts by mass of distilled water (temperature = 25 ° C.) were mixed together, and the multiple cores were washed with the distilled water (washing time = 15 minutes), and then the multiple cores were dried (drying time = 130 ° C.).

[0298] Next, 100 parts by mass of the multiple cores, 0.1 part by mass of polyvinylidene fluoride (PVDF), and 0.9 part by mass of aluminum hydroxide (Al(OH)3) were mixed together to obtain a mixture.

[0299] Finally, the mixture was heated (heating temperature = 600 ° C.) to form a coating portion containing polyvinylidene fluoride and aluminum hydroxide on the surface of each of the multiple core portions, thereby forming multiple positive electrode active material particles including a core portion and a coating portion.

[0300] Thirdly, as described below, a secondary battery was fabricated using the same procedure as disclosed in the above-mentioned Patent Document 4 (JP Patent Publication No. 2013-062026), except that multiple positive electrode active material particles were formed using the procedure disclosed therein (Comparative Example 4).

[0301] When forming a plurality of positive electrode active material particles, the same procedure as that of Example 1 was used, except that a precursor layer was formed using only a plurality of central parts (LNCM) without using a boron oxygen-containing material and a carbon oxygen-containing material, and then a coating part was formed on each surface of the plurality of central parts by using a stabilization treatment of the secondary battery after assembly. In this case, instead of forming an upper coating part and a lower coating part, a coating part containing a decomposition product of an electrolyte salt (lithium hexafluorophosphate) contained in the electrolyte was formed, and thus a plurality of positive electrode active material particles including a central part and a coating part were formed. This coating part is a coating film formed on each surface of the plurality of central parts in the stabilization treatment.

[0302] After the secondary battery was completed, the content (mol %) was examined, and the results are shown in Table 1.

[0303] In addition, after the secondary battery was completed, a depth analysis of the test electrode 61 using TOF-SIMS was performed to check whether each of the three physical property conditions for the physical properties of the test electrode 61 was satisfied. The results are shown in Table 1.

[0304] [Evaluation of battery characteristics] The heat resistance characteristic as one of the battery characteristics was evaluated according to the procedure described below, and the results shown in Table 1 were obtained.

[0305] When evaluating the heat resistance characteristics, a thermal stability evaluation test was performed using a secondary battery as described below to examine the environmental temperature (° C.), which is an index for evaluating the heat resistance characteristics.

[0306] First, the secondary battery was charged in the air at normal temperature and humidity (temperature = 23°C, humidity = 30%). In this case, it was charged at a constant current of 0.1 C until the voltage reached 4.25 V, and then it was charged at a constant voltage of 4.25 V until the current reached 0.01 C.

[0307] Next, the secondary battery in a charged state was disassembled to collect the test electrode 61 and the electrolyte. Next, the positive electrode current collector was peeled off from the positive electrode active material layer, and then the sample (positive electrode active material layer and electrolyte) was sealed in an aluminum sample pan for thermal analysis.

[0308] Finally, the sample pan was attached to a differential scanning calorimeter (DSC), and the sample was subjected to thermal analysis using the differential scanning calorimeter to identify the environmental temperature (°C) at which the maximum exothermic peak was detected. In this case, a Hitachi High-Tech DSC6300 differential scanning calorimeter was used as the differential scanning calorimeter, and the heating rate was set to 10°C / min.

[0309] When the lithium composite oxide, which is the positive electrode active material, is heated inside the differential scanning calorimeter, it releases heat due to the collapse of the crystal structure. As a result, the maximum exothermic peak is a peak detected due to the heat released from the lithium composite oxide. Therefore, the environmental temperature at which the maximum exothermic peak is detected represents the thermal stability of the lithium composite oxide, that is, the temperature to which the crystal structure can withstand when the lithium composite oxide is heated.

[0310] Therefore, the higher the environmental temperature, the higher the thermal stability of the lithium composite oxide, and therefore the less likely the temperature of the test electrode 61 will rise excessively during overcharging, heating of the secondary battery, occurrence of an internal short circuit, etc. On the other hand, the lower the environmental temperature, the lower the thermal stability of the lithium composite oxide, and therefore the more likely the temperature of the test electrode 61 will rise excessively during overcharging, heating of the secondary battery, occurrence of an internal short circuit, etc.

[0311] [Table 1]

[0312] [Consideration] As shown in Table 1, when the test electrode 61 contained a lithium composite oxide and the content of the lithium composite oxide was 80 mol % or more, the environmental temperature varied depending on the physical properties of the test electrode 61 .

[0313] Specifically, when the three types of physical property conditions for the test electrode 61 were not all satisfied (Comparative Examples 1 to 4), the environmental temperature decreased. In contrast, when the three types of physical property conditions for the test electrode 61 were all satisfied (Examples 1 and 2), the environmental temperature increased.

[0314] In particular, when all three types of physical property conditions regarding the physical properties of the test electrode 61 were satisfied (Examples 1 and 2), the following tendency was obtained.

[0315] First, the environmental temperature increased when the coating portion included an upper coating portion and a lower coating portion, in which case the environmental temperature increased sufficiently when the upper coating portion included lithium fluoride and the lower coating portion included lithium metaborate.

[0316] Second, the environmental temperature increased regardless of the composition of the lithium composite oxide. In this case, the environmental temperature increased sufficiently even if the lithium composite oxide contained other elements as constituent elements.

[0317] <Examples 3 to 5 and Comparative Examples 5 and 6> As shown in Table 2, a secondary battery was fabricated in a similar manner, except that a boron-fluorine-containing material (lithium tetrafluoroborate) was added to the electrolyte, and the battery characteristics were then evaluated.

[0318] In this case, the boron-fluorine-containing material was added to the electrolyte, and then the electrolyte was stirred. The content (wt%) of the boron-fluorine-containing material in the electrolyte is as shown in Table 2.

[0319] [Table 2]

[0320] Even when the electrolyte contained a boron-fluorine-containing material (Table 2), the same results were obtained as when the electrolyte did not contain a boron-fluorine-containing material (Table 1). That is, when all three types of physical property conditions were satisfied for the physical properties of the test electrode 61 (Examples 3 to 5), the environmental temperature increased compared to when all three types of physical property conditions were not satisfied for the physical properties of the test electrode 61 (Comparative Examples 5 and 6).

[0321] In particular, when the electrolyte contained a boron-fluorine-containing material (Example 3), the environmental temperature rose more than when the electrolyte did not contain a boron-fluorine-containing material (Example 1).

[0322] [summary] From the results shown in Tables 1 and 2, the environmental temperature rose when the positive electrode active material layer 21B of the test electrode 61 contained a plurality of positive electrode active material particles 210, the positive electrode active material particles 210 contained a central portion 211 and a coating portion 212, the central portion 211 contained a lithium composite oxide having a layered rock-salt crystal structure, the content ratio C of the lithium composite oxide was 80 mol% or more, the electrolyte salt of the electrolyte solution contained a fluorine-containing lithium salt, and all three types of physical property conditions were satisfied regarding the physical properties of the test electrode 61. Thus, when a lithium composite oxide with the content ratio C of 80 mol% or more was used, the heat resistance characteristics were improved, and excellent safety was obtained.

[0323] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the present technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.

[0324] Specifically, the battery structure of the secondary battery has been described as being of a laminate film type and a coin type. However, the battery structure of the secondary battery is not particularly limited, and may be of a cylindrical type, a square type, a button type, or the like.

[0325] Also, the battery element has been described as having a wound structure. However, the structure of the battery element is not particularly limited, and may be a stacked structure or a zigzag structure. In the stacked structure, the positive and negative electrodes are alternately stacked with a separator interposed therebetween, and in the zigzag structure, the positive and negative electrodes are folded in a zigzag pattern while facing each other with the separator interposed therebetween.

[0326] Although the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, the electrode reactant may be other alkali metals such as sodium and potassium, as described above, or alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.

[0327] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.

[0328] The present technology can also be configured as follows. <1> a positive electrode including a positive electrode active material layer; A negative electrode; An electrolyte solution containing an electrolyte salt; Equipped with the positive electrode active material layer includes a plurality of positive electrode active material particles, The positive electrode active material particles are a core portion including a lithium composite oxide; a covering portion provided on a surface of the central portion; Including, The lithium composite oxide has a layered rock salt type crystal structure and contains lithium, nickel and other elements as constituent elements, the coating portion contains lithium, fluorine, boron, and oxygen as constituent elements; the electrolyte salt comprises a fluorine-containing lithium salt; the content of the nickel in the lithium composite oxide is 80 parts by mol or more and 100 parts by mol or less, where the sum of the content of the nickel in the lithium composite oxide and the content of the other element in the lithium composite oxide is taken as 100 parts by mol; In the analysis of the positive electrode active material layer in the depth direction using time-of-flight secondary ion mass spectrometry, LiF2 - The first negative secondary ions and BO2 - A second negative secondary ion was detected, which was derived from a change in ion intensity of the first negative secondary ion in the depth direction has a first peak, and a change in ion intensity of the second negative secondary ion in the depth direction has a second peak; The second peak is located deeper than the first peak in the depth direction. Secondary battery. <2> The covering portion includes, in order from the side farther from the center portion, A first coating portion containing lithium and fluorine as constituent elements; A second coating portion containing lithium, boron and oxygen as constituent elements; Including, <1> The secondary battery according to claim 1. <3> The first coating portion contains lithium fluoride (LiF), The second coating portion contains lithium metaborate (LiBO2). <2> The secondary battery according to claim 1. <4> The other elements include at least one of cobalt, aluminum, manganese, zirconium, titanium, molybdenum, tantalum, chromium, niobium, iron, copper, zinc, vanadium, magnesium, tungsten, sulfur, strontium, boron, sodium, and fluorine. <1> Or <3> 13. The secondary battery according to claim 12, <5> The fluorine-containing lithium salt includes at least one of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiN(FSO2)2); <1> Or <4> 13. The secondary battery according to claim 12, <6> The electrolyte further comprises a boron fluorine-containing material; <1> Or <5> 13. The secondary battery according to claim 12, <7> The boron-fluorine-containing material includes at least one of lithium tetrafluoroborate (LiBF4) and lithium difluoro(oxalato)borate (LiBF2(C2O4)); <6> The secondary battery according to claim 1. <8> It is a lithium-ion secondary battery. <1> Or <7> 13. The secondary battery according to claim 12, [Explanation of symbols]

[0329] 21 ... positive electrode, 21B ... positive electrode active material layer, 22 ... negative electrode, 210 ... positive electrode active material particles, 211 ... center portion, 212 ... coating portion, 212A ... upper coating portion, 212B ... lower coating portion.

Claims

1. a positive electrode including a positive electrode active material layer; A negative electrode; An electrolyte solution containing an electrolyte salt; Equipped with the positive electrode active material layer includes a plurality of positive electrode active material particles, The positive electrode active material particles are a core portion including a lithium composite oxide; a covering portion provided on a surface of the central portion; Including, The lithium composite oxide has a layered rock salt type crystal structure and contains lithium, nickel and other elements as constituent elements, the coating portion contains lithium, fluorine, boron, and oxygen as constituent elements; the electrolyte salt comprises a fluorine-containing lithium salt; the content of the nickel in the lithium composite oxide is 80 parts by mol or more and 100 parts by mol or less, where the sum of the content of the nickel in the lithium composite oxide and the content of the other element in the lithium composite oxide is taken as 100 parts by mol; In the analysis of the positive electrode active material layer in the depth direction using time-of-flight secondary ion mass spectrometry, 2 - The first negative secondary ions and BO 2 - A second negative secondary ion is detected, which is derived from a change in ion intensity of the first negative secondary ion in the depth direction has a first peak, and a change in ion intensity of the second negative secondary ion in the depth direction has a second peak; The second peak is located deeper than the first peak in the depth direction. Secondary battery.

2. The covering portion includes, in order from the side farther from the center portion, A first coating portion containing lithium and fluorine as constituent elements; A second coating portion containing lithium, boron and oxygen as constituent elements; The secondary battery according to claim 1 .

3. The first coating portion contains lithium fluoride (LiF), The second coating portion is made of lithium metaborate (LiBO 2 ), The secondary battery according to claim 2 .

4. The other elements include at least one of cobalt, aluminum, manganese, zirconium, titanium, molybdenum, tantalum, chromium, niobium, iron, copper, zinc, vanadium, magnesium, tungsten, sulfur, strontium, boron, sodium, and fluorine. The secondary battery according to claim 1 .

5. The fluorine-containing lithium salt is lithium hexafluorophosphate (LiPF 6 ) and lithium bis(fluorosulfonyl)imide (LiN(FSO 2 ) 2 ) at least one of The secondary battery according to claim 1 .

6. The electrolyte further comprises a boron fluorine-containing material; The secondary battery according to claim 1 .

7. The boron-fluorine-containing material is lithium tetrafluoroborate (LiBF 4 ) and lithium difluoro(oxalato)borate (LiBF 2 (C 2 O 4 )) The secondary battery according to claim 6.

8. It is a lithium-ion secondary battery. The secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Positive active material, its manufacturing method, and battery

    JP2006351487A

  • Lithium ion secondary battery and manufacturing method therefor

    JP2013062026A

  • Positive electrode active material, positive electrode, and nonaqueous electrolyte secondary battery

    JP2015099659A

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2022525463A